Integration of electrocoagulation and solar energy for sustainable wastewater treatment: a thermodynamic and life cycle assessment study - Cetinkaya, Afsin Yusuf (SPRINGER, 2025)
This study presents an innovative approach to sustainable wastewater treatment by integrating electrocoagulation (EC) with solar energy and biogas. The research evaluates the performance of an EC reactor in terms of chemical oxygen demand (COD) removal efficiency under varying current densities, demonstrating enhanced COD removal rates with increased current densities, achieving up to 95.3% at 1500 A/m2. Life cycle assessment (LCA) is employed to compare the environmental impacts of different energy sources for powering the EC system. The findings indicate that biogas derived from domestic waste offers a lower environmental impact compared to natural gas, coal, hydro, solar, and wind. The study further explores the potential of solar energy in Turkey, particularly in Istanbul, where high solar radiation could be harnessed. However, the efficiency of photovoltaic (PV) panels is affected by temperature, with an observed efficiency decrease of approximately 0.5% per degree Celsius increase in temperature. Effective cooling strategies are thus essential for optimizing PV performance. The integration of EC with solar energy, powered by biogas, not only enhances wastewater treatment efficiency but also contributes to reduced greenhouse gas emissions and energy costs. This combined approach presents a viable solution for both domestic and industrial wastewater treatment, especially in remote or off-grid areas.
Keywords: Life cycle assessment; SimaPro; Electrocoagulation; Renewable energy; TEMPERATURE; GENERATION; SYSTEM; Environmental Sciences & Ecology